Analytical band Monte Carlo simulation of electron impact ionization in In[sub 0.53]Ga[sub 0.47]As - Choo, K. Y.; Ong, D. S. (2004)
An analytical band Monte Carlo model has been developed to study electron transport and impact ionization in In0.53Ga0.47As. Our simulations show that it is important to include the second conduction band at X-7 because impact ionization becomes significant in this higher band at fields above 100 kV/cm. The higher ionization rate here is found to be responsible for the strong field dependence of the ionization coefficient for electric fields above 180 kV/cm. At lower fields the weak field dependence results from the large energy separation between the Gamma(6) and X-7 valleys which confines most of the electrons to the first conduction band, where the ionization rate is lower. Although the electron impact ionization coefficient of InGaAs is comparable to that of GaAs at 300 kV/cm, the average electron energy at impact ionization is 1.59 eV lower than in GaAs and the average time to impact ionization is almost twice that in GaAs, indicating a slower drift of electrons in InGaAs prior to impact ionization. (C) 2004 American Institute of Physics.